Effects of two-stage preterm formulas on growth, nutritional biomarkers, and neurodevelopment in preterm infants - Kwinta, Przemko; Lazarova, Svilena; Demová, Klaudia; Chen, Yipu; Hartweg, Mickaël; Krattinger, Laura-Florina; Fumero, Cecilia; Buczyńska, Aleksandra; Durlak, Wojciech; Uhrikova, Zuzana; Kozar, Marek; Samuel, Tinu Mary; et al. (Frontiers in Pediatrics, 2024)
Background: Formula-fed preterm infants require nutrient-enriched formulas with optimized protein levels to support growth and neurodevelopment. The purpose of this study was to evaluate the safety, tolerability, and effectiveness of a new liquid two-staged formula system designed to provide tailored nutrition during hospital stay and after discharge.Methods: Male and female very-low-birth-weight preterm infants (birth weight≤1500g; gestational age≤32 weeks) were recruited from 3 neonatal units in Poland and Slovakia in a prospective, openlabel, interventional study. Stage 1 formula providing 3.6g intact protein/100kcal was consumed from enrolment until reaching 1800g, followed by a post-discharge (PD) Stage 2 formula with 2.8g/100kcal protein which was consumed for 30 days PD. Weight gain velocity (WGV; g/kg/day) from FEF D1 (first day of achieving Full Enteral Feeding rate of 150mL/kg/day and cessation of parenteral feeding) and day reaching 1800g was compared to the minimally required WGV (15 g/kg/day) for non-inferiority (primary endpoint), and to the Fenton median growth rate for superiority (17.3g/kg/day), adjusting for sex, gestational age, site, visit, and WGV. Changes in z-scores, feeding tolerance, nutritional biomarker status, and safety were also assessed from FEF D1 to 30 days PD. In an observational follow-up at 2 years of age, neurodevelopment was evaluated using the Bayley Scales of Infant and Toddler Development (BSID-III).Results: Adjusted weight gain velocity (95% CI) between the first day of full enteral feeding and 1800g in PP (N=18, per-protocol) was 23.0 (20.1, 25.9) g/kg/day; lower limit of the 95% CIs exceeded the non-inferiority margin (15g/kg/day, p<0.001) and the superiority margin (17.3g/kg/day, p<0.001). Mean stool frequency ranged from 2.5-3.3 stools per day. The two-stage formula supported adequate growth patterns through the study and nutritional biomarkers of protein and mineral status were within normal ranges. At 24 months corrected age, the mean±SD of the BSID cognitive scale was 97.3±13.9 in PP, with all infants achieving a score >70. None of the adverse events reported were related to the study formulas.The two-stage preterm formulas supported postnatal weight gain, adequate growth, cognitive development within normal ranges, and a safe profile of protein and bone biomarkers.